3(m-4)=11

Simple and best practice solution for 3(m-4)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(m-4)=11 equation:



3(m-4)=11
We move all terms to the left:
3(m-4)-(11)=0
We multiply parentheses
3m-12-11=0
We add all the numbers together, and all the variables
3m-23=0
We move all terms containing m to the left, all other terms to the right
3m=23
m=23/3
m=7+2/3

See similar equations:

| 2x+10=13-× | | 3(2-3x)=2(3x+5) | | 14+2(x-1)=16 | | 4/5x=3/4x+4 | | 6s+41=149 | | 7x-2=5x-28 | | 4x+7=-x-5 | | 4n(n)=2 | | 16=y/6-1 | | 7x+4x=19+3 | | (x-7)(2x+3)=2x2+100 | | 4x+9-5=0 | | (x-7)(2x+3)=2x+100 | | 5z=2.5+4.5 | | 89b-35=411 | | 5(2x)-3=20x+5 | | (2t-5)^2-6=0 | | 9x-45=9•(x-5) | | 10(s-10)=-178 | | 10s-100=-178 | | -12=x/5-12 | | 12.2h-0.5=12.92 | | (4x+1)^2-(2x–3)(3x+2)=0 | | 2(x+50)/3=4(2x+30)/3 | | -m/12-6=4 | | 1f-4=-2f+6 | | F-4=-2f-6 | | 141=4x+(6x+5) | | 3/2x+2=32 | | 18=k/2-1 | | y′′-8y′+15y=0 | | (x-5)²+(2x+3)²=(x+1)²+97 |

Equations solver categories